The Main Directions for the Development of Household Services of Rural Areas - Makhmudov Jasurbek Ergashevich; Kubaev Odil Utkirovich (International Journal on Integrated Education, 2022)
This article describes the state and development trends of consumer services in rural areas. On the basis of a set of additional measures for the development of the service sector, the main directions of consumer services are proposed.